PERBANDINGAN INOVASI PRODUK ANTARA SMARTHPHONE OPPO DAN VIVO (STUDI PADA PENGGUNA SMARTHPHONE OPPO DAN VIVO DI KOTA BIMA) - Sukmawati Sukmawati; Sri Ernawati (Jurnal Bina Bangsa Ekonomika, 2021)
Product innovation can increase the added value of a product, so this will affect consumers in determining purchasingdecisions. This research aims to  find out whether  there is a difference in  Product Innovation Between OPPO Smarthphone and VIVO (Study on Oppo And VIVO Smarthphone Users in Bima City). This type of research is  descriptive. The research instrument used is a  likert scale questionnaire that has been shared. The population in this study is  all consumers of Oppo Smarthphone users  and VIVO in Bima Citywhose numbers are not yet known for sure (Unknow population). The number of samples in  this study was 30  respondents  for each object or subject of the study, so that the overall sample number was 60 respondents  with accidental sampling techniques. The data collection techniques used are observations, questionnaires and literature studies. Data analysis techniques used are valid, reliability test, different test (t-test). The results of the study showed that  there is no difference in Product Innovation Between OPPO Smarthphone and VIVO (Study on Oppo And VIVO Smarthphone Users in Bima City)